Optimalisasi Manajemen Pelatihan bagi Penyuluh Agama dalam Meningkatkan Efektivitas Bimbingan Perkawinan dan Pencegahan Bullying di Kantor Kementerian Agama Kabupaten Nganjuk - Maghfiroh, Binti Asirotul; Uut Nur Laili; Hafidhoh, Yulia (Welfare : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to optimize training management for religious instructors in increasing the effectiveness of marriage guidance and Bullying prevention. Religious instructors have a strategic role in guiding the community towards a harmonious family life and creating a safe and conducive social environment. However, there are still obstacles in the counseling method which is less systematic and less than optimal in the use of digital media. This activity was carried out at the Office of the Ministry of Religion of Nganjuk Regency on June 25-26, 2024, using the Participatory Action Research (PAR) method which involved training sessions, interactive discussions, and practical simulations. The results of the activity showed an increase in participant understanding by 40%-50%, as well as an increase in skills in utilizing technology for counseling. With this training, religious instructors are better prepared to provide marriage guidance and address Bullying cases in the community more effectively and systematically.